2011
DOI: 10.1111/j.1600-079x.2011.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation of molecular, dietary, and metabolic signaling mechanisms of human breast cancer growth by the nocturnal melatonin signal and the consequences of its disruption by light at night

Abstract: This review article discusses recent work on the melatonin-mediated circadian regulation and integration of molecular, dietary and metabolic signaling mechanisms involved in human breast cancer growth and the consequences of circadian disruption by exposure to light-at-night (LAN). The antiproliferative effects of the circadian melatonin signal are mediated through a major mechanism involving the activation of MT1 melatonin receptors expressed in human breast cancer cell lines and xenografts. In estrogen recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
138
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 64 publications
1
138
3
1
Order By: Relevance
“…It has also been shown that melatonin at physiological levels suppresses the proliferation of human breast cancer xenografts (15)(16)(17). Furthermore, melatonin may reduce the invasiveness of human breast cancer, and the suppression of melatonin during the biological night may act as a promoter of oncogenesis (10,16). This experimental evidence suggests that suppression of melatonin from night shift work may exert its response downstream the complex casual pathways that lead to breast cancer.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…It has also been shown that melatonin at physiological levels suppresses the proliferation of human breast cancer xenografts (15)(16)(17). Furthermore, melatonin may reduce the invasiveness of human breast cancer, and the suppression of melatonin during the biological night may act as a promoter of oncogenesis (10,16). This experimental evidence suggests that suppression of melatonin from night shift work may exert its response downstream the complex casual pathways that lead to breast cancer.…”
mentioning
confidence: 80%
“…From animal studies it is known that melatonin reduces the growth of chemically induced mammary tumors (10,14). It has also been shown that melatonin at physiological levels suppresses the proliferation of human breast cancer xenografts (15)(16)(17). Furthermore, melatonin may reduce the invasiveness of human breast cancer, and the suppression of melatonin during the biological night may act as a promoter of oncogenesis (10,16).…”
mentioning
confidence: 99%
“…In these recent studies, the addition of MLT to the drinking water blocked the accelerated tumor growth effects of ALAN. In rodent models of tumorigeneses, the metastasis formation of solid tumors increased in response to pinealectomy and induced-metastatic surgery effect, whereas pharmacological MLT administration reversed the formation [201]. In MCF-7 human breast-cancer cell lines, MLT administration reduced the tumor invasion potential [202], and in MCF-7 tumor-bearing mice, MLT lessened metastasis formation compared with counterpart untreated mice [203].…”
Section: Mlt and Cancermentioning
confidence: 99%
“…MLT can affect breast cancer cell development by blocking the linoleic acid uptake via MT1-induced cyclic adenosine monophosphate (cAMP) suppression; this promotes the downregulation of the mitogenic signaling molecule 13-hydroxyoctadecadienoic that is responsible for the activation of growth factor pathways that are essential for cells growth and survival [201]. MLT can modulate the expression patterns of different core clock genes and other circadian-related genes involved in cellular carcinogenic activities [209].…”
Section: Mlt and Cancermentioning
confidence: 99%
See 1 more Smart Citation